Deep Herpes. (29th October 2021) - Krystel-Whittemore, Melissa; Chan, May P.; Shalin, Sara C.; Sauder, Kenan J.; Hudson, Amy; Foreman, Ruth K.; Hoang, Mai P.; Brennick, Jeoffry B.; Yan, Shaofeng; Nazarian, Rosalynn M.
Abstract : Supplemental Digital Content is available in the text. Abstract : Herpes viruses are known for infecting epithelial cells and manifesting as vesicles. However, herpes viruses can also infect stromal cells. While established in the ocular setting, cutaneous stromal herpes (deep herpes) is previously unreported and may evade clinical and microscopic detection. We searched for skin biopsies with herpes stromal disease. Clinical information was retrieved via electronic medical records and pathology records system. Hematoxylin and eosin slides, immunohistochemical staining, and polymerase chain reaction detection of viral DNA was performed. We identified 12 specimens from 10 patients with cutaneous stromal herpes simplex virus 1/2 (n=7) or varicella-zoster virus infection (n=5). The most common site involved was the buttocks/perianal region (n=6). Ulceration was a frequent dermatologic finding (n=8). Pyoderma gangrenosum was clinically suspected in 6 specimens (50%). Eight patients (80%) were immunosuppressed. Biopsies frequently demonstrated a dense dermal mixed inflammatory infiltrate with subcutaneous extension and enlarged cells with viral cytopathic changes confirmed by herpes simplex virus 1/2 or varicella-zoster virus immunohistochemistry (n=10) or polymerase chain reaction (n=2). Most specimens (67%) lacked evidence of characteristic epidermal keratinocyte infection. This study presents the first known report of the ability of herpes virus to infect deep stromal cells of the dermis. We raise awareness of cutaneous stromal herpes in patients presenting with atypical clinical lesions, particularly while immunocompromised. Establishing the correct diagnosis is critical for initiating therapy.